2010
DOI: 10.1161/hypertensionaha.109.141937
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Vascular Endothelial Growth Factor 121 Infusion Lowers Blood Pressure and Improves Renal Function in Rats With PlacentalIschemia-Induced Hypertension

Abstract: Abstract-Antagonism of vascular endothelial growth factor (VEGF) signaling by soluble fms-like tyrosine kinase 1 occurs during preeclampsia and is proposed to play an important role in the pathogenesis of preeclampsia. We reported recently that hypertension associated with chronic reductions in uteroplacental perfusion pressure (RUPP) is associated with increased soluble fms-like tyrosine kinase 1 and decreased free VEGF. Key Words: preeclampsia Ⅲ gestation Ⅲ VEGF Ⅲ blood pressure Ⅲ angiogenic P reeclampsia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
134
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 38 publications
13
134
3
Order By: Relevance
“…We found that spiking the ELISA standard curves with ELP‐VEGF reduced the signal, suggesting that ELP‐VEGF might bind the Flt‐1 in the assay and prevent binding of 1 or both antibodies, thus confirming this as an assay for free sFlt‐1. Again, RUPP surgery resulted in a significant increase in free plasma sFlt‐1 (Figure 4C), consistent with previous reports 32, 36, 53, 56, 58, 63, 68. In contrast to the Western blot data, the ELISA data showed that ELP‐VEGF‐treated rats (both sham and RUPP surgical groups) had markedly reduced free sFlt‐1 levels (Figure 4C).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We found that spiking the ELISA standard curves with ELP‐VEGF reduced the signal, suggesting that ELP‐VEGF might bind the Flt‐1 in the assay and prevent binding of 1 or both antibodies, thus confirming this as an assay for free sFlt‐1. Again, RUPP surgery resulted in a significant increase in free plasma sFlt‐1 (Figure 4C), consistent with previous reports 32, 36, 53, 56, 58, 63, 68. In contrast to the Western blot data, the ELISA data showed that ELP‐VEGF‐treated rats (both sham and RUPP surgical groups) had markedly reduced free sFlt‐1 levels (Figure 4C).…”
Section: Resultssupporting
confidence: 90%
“…These bands correspond to the report of Rajakumar,67 who describes sFlt‐1 bands of 145, 100, and 60 kDa in plasma from preeclamptic patients, though considerable species and glycosylation variation could exist. The RUPP surgery leads to a significant increase in plasma sFlt‐1, as has previously been reported 32, 36, 53, 56, 58, 68. This was confirmed in a separate cohort of rats, treated entirely independently with the sham or RUPP surgeries, and analyzed in a separate Western blot (Figure S1).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations